PENGARUH NET FROFIT MARGIN, RETURN ON ASSETS DAN RETURN ON EQUITY TERHADAP PRICE TO BOOK VALUE PADA PERUSAHAAN TELEKOMUNIKASI SELULER YANG TERCATAT DI BURSA EFEK INDONESIA TAHUN 2014-2023 - Muntaki; Mutawali (Journal of Research and Publication Innovation, 2025)
This research aims to determine the extent and significance of the influence of Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) on Price to Book Value (PBV) in cellular telecommunication companies listed on the Indonesia Stock Exchange (IDX). This study employs a descriptive quantitative approach with panel data regression analysis, utilizing a 10-year time series from 2014-2023, involving four cellular telecommunication companies. Based on the E-views 13 test results, the partial test (t-test) indicates that the Net Profit Margin variable has no significant influence on Price to Book Value, as evidenced by a t-statistic of -0.924271, which is less than the t-table value of 2.02809. Conversely, the Return on Assets variable is found to have a significant influence on Price to Book Value, with a t-statistic of 3.155403, which is greater than the t-table value of 2.02809. The Return on Equity variable, however, does not significantly influence Price to Book Value, as its t-statistic of 0.520607 is less than the t-table value of 2.02809. Nevertheless, simultaneously (F-test), Net Profit Margin, Return on Assets, and Return on Equity collectively have a positive and significant influence on Price to Book Value. This is supported by an F-statistic of 21.85671, which exceeds the F-table value of 2.87, contributing 61,6029%,  to the change in PBV, while the remaining 38.3771% is influenced by external factors not included in this study.